Salvage of a failed valgus osteotomy for non-union of an unstable pertrochanteric fracture - Watanabe, Y. (Springer-Verlag, 2006)
Salvage of a failed valgus osteotomy for nonunion of an unstable pertrochanteric fracture is reported. A valgus intertrochanteric osteotomy was performed for a failed sliding hip screw fixation of an unstable pertrochanteric fracture at another institution. Four months following osteotomy, the fracture was still un-united with two distal screws of the hip plate broken and a coxa vara deformity. Reconstruction was performed with a nine-hole 95° angle blade plate and cancellous bone graft, because the insufficient fixation of the distal fragment was considered to be the main reason for failure. The osteotomy was healed at six months post-surgery and the patient reported complete resolution of symptoms. Intertrochanteric valgus osteotomy is an effective procedure for mal-union and non-union of pertrochanteric fracture but stable fixation is required for a good result. The blade of the angle plate offers good purchase of the proximal fragment and secures it under rotational and bending stresses. We recommend that distal fragments should be fixed with at least seven cortices for this type of osteotomy.